Data transmission latency mathematical model in an SDN-controlled 5G network - Kadatskaya, O.I.; Saburova, S.A. (Radiotekhnika, 2025)
Next-generation services are considered and grouped into the following categories: enhanced mobile broadband access, massive connectivity and machine-type data exchange, and ultra-reliable communication with low latency. To support these diverse service delivery scenarios, 5G networks must meet the key requirements of the Quality of Service (QoS) system. The technologies and main configuration methods of SDN OpenFlow controllers interacting with the data processing center of the 5G network are examined. OpenFlow is the primary protocol of SDN architecture. Controllers use the OpenFlow protocol to communicate with switches (forwarding devices). OpenFlow is vendor-independent, meaning the controller can interact with any switch regardless of its manufacturer. Quality indicators calculations and probabilistic–temporal analysis of information processing are typically performed at the data processing center of the distributed control system for controlled objects (CO), based on an interaction model between each user and the RAP, with OpenFlow protocol support via the SDN platform for 5G networks.Failures in the operation of SDN controllers are minimized through timely decision-making aimed at ensuring reliability and security indicators for the functioning of controlled consumer (CO)objects within 5G networks. At the data processing center of the distributed control system for controlled objects based on the OpenFlow SDN platform in 5G networks, the key tasks involve calculating the specified delay metrics using a dedicated mathematical model. A model has been proposed, followed by computation, analysis, and assessment of data transmission latency during the management of 5G network elements on the SDN platform and recommendations are provided for selecting a control system configuration scenario.